Hazard identification of pyrogenic synthetic amorphous silica (NM-203) after sub-chronic oral exposure in rat: A multitarget approach. (March 2020) - Tassinari, Roberta; Di Felice, Gabriella; Butteroni, Cinzia; Barletta, Bianca; Corinti, Silvia; Cubadda, Francesco; Aureli, Federica; Raggi, Andrea; Narciso, Laura; Tait, Sabrina; Valeri, Mauro; Martinelli, Andrea; et al.
Abstract: Food additive E551 consists of synthetic amorphous silica (SAS), comprising agglomerates and aggregates of primary particles in the nanorange (<100 nm), which potential nanospecific risks for humans associated to dietary exposure are not yet completely assessed. In NANoREG project, aim of the study was to identify potential hazards of pyrogenic SAS nanomaterial NM-203 by a 90-day oral toxicity study (OECD test guideline 408). Adult Sprague-Dawley rats of both sexes were orally treated with 0, 2, 5, 10, 20 and 50 mg SAS/kg bw per day; dose levels were selected to be as close as possible to E551 dietary exposure. Several endpoints were investigated, the whole integrative study is presented here along with the results of dispersion characterization, tissue distribution, general toxicity, blood/serum biomarkers, histopathological and immunotoxicity endpoints. No mortality, general toxicity and limited deposition in target tissues were observed. NM-203 affected liver and spleen in both sexes. Proposed NOAEL 5 mg/kg bw per day in male rats for enlarged sinusoids in liver. In female rats, TSH and creatinine levels were affected, proposed LOAEL 2 mg/kg bw per day. Overall, these data provide new insight for a comprehensive risk assessment of SAS exposure by the oral route. Graphical abstract: Image 1 Highlights: Food additive E551 is a nanomaterial consisting in synthetic amorphous silica. Health risks associated to E551 are not fully assessed yet. 90-day oral toxicity study with pyrogenic synthetic amorphous silica is performed. Rats are treated with realistic dose levels: 2, 5, 10, 20, 50 mg/kg bw per day. NOAEL 5 mg/kg bw per day in male rats, LOAEL 2 mg/kg bw per day in female rats.